Overlapping Chancre and Syphilitic Roseola in an Immunocompetent Patient: A Case Report - Qaira Anum; Vesri Yossy; Agung Bima Putera (Scientific Journal, 2026)
Background: Syphilis is a sexually transmitted infection caused by Treponema pallidum that typically progresses through primary, secondary, latent, and tertiary stages. Primary syphilis presents with a painless genital chancre, whereas secondary syphilis manifests with systemic and mucocutaneous findings. Overlapping primary and secondary syphilis is uncommon and is rarely reported in immunocompetent individuals.  Case: A 38-year-old immunocompetent man presented with a painless penile ulcer that progressively enlarged over two months, accompanied by non-pruritic erythematous macules with whitish scaling on both palms for one month. Physical examination revealed a solitary, shallow, indurated genital ulcer with well-defined borders and palmar macules. Dermoscopy demonstrated “Biett’s collarette”. Serological testing showed reactive VDRL (1:32) and TPHA (1:5120), with a non-reactive HIV test. Histopathological examination of the penile ulcer revealed epidermal ulceration, dense perivascular plasma cell and lymphohistiocytic infiltration, and endarteritis obliterans, consistent with syphilitic ulcer. Urethral culture identified Neisseria gonorrhoeae, indicating concomitant gonococcal urethritis. The patient was diagnosed with overlapping primary and secondary syphilis with gonorrhea co-infection and was treated with intramuscular benzathine penicillin G, oral cefixime, and azithromycin, resulting in marked clinical improvement.  Discussion: Persistence of the chancre beyond the expected healing period together with concurrent palmar syphilitic roseola supports stage overlap rather than sequential progression. Delayed diagnosis and coexisting gonococcal infection may have contributed to this presentation despite preserved immune status. Conclusion: Overlapping primary and secondary syphilis can occur in immunocompetent patients. Recognition of this atypical presentation and comprehensive clinicopathological correlation are essential to ensure accurate diagnosis and appropriate management.